Health service searched by people with tuberculosis symptoms - Martina Dias da Rosa Martins; Natali Basílio Valerão; Jéssica Oliveira Tomberg; Lílian Moura de Lima Spagnolo; Luciana Nunes Soares; Roxana Isabel Cardozo Gonzales (Universidade Federal de Santa Maria, 2019)
Objetive: to identify the profile of people with tuberculosis in relation to the behavior of search for care against the first symptoms of the disease. Method: quantitative study developed in four cities of Rio Grande do Sul, between 2013 and 2014, with the application of a structured questionnaire to people with pulmonary tuberculosis who began treatment within the period. Data analysis was performed in Statistica 12 software, using descriptive statistics. Results: the most sought after health service was prompt care (35.7%). Regarding the profile, there was a predominance of males (58.7%), white skin color (59.8%), who lived without a partner (67.4%), education less than 8 years (75.0%), formal employment (41.3%), income from 1 to 2 minimum wages (43.5%). Conclusion: there were differences in the profile according to the behavior of search for care, and it is noted that knowing it is essential for the planning of early diagnosis actions.